2014
DOI: 10.1016/j.toxrep.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol, a prenylated flavonoid from hops ( Humulus lupulus L.), protects rat tissues against oxidative damage after acute ethanol administration

Abstract: Ethanol-mediated free radical generation is directly involved in alcoholic liver disease. In addition, chronic alcohol bingeing also induces pathological changes and dysfunction in multi-organs. In the present study, the protective effect of xanthohumol (XN) on ethanol-induced damage was evaluated by determining antioxidative parameters and stress oxidative markers in liver, kidney, lung, heart and brain of rats. An acute treatment (4 g/kg b.w.) of ethanol resulted in the depletion of superoxide dismutase, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…In this study, the decrease in the reduced glutathione level in the ethanol group is connected with ethanol induced oxidative stress and direct conjugation of GSH with acetaldehyde and other reactive intermediates of alcohol oxidation. The result of the present study agrees with the finding of Pinto et al [41] who reported that acute ethanol treatment caused reduction in the glutathione levels in different tissues. The significant increase ( P < 0.1) in the glutathione levels in the liver and brain of water melon juice treated rats prior to ethanol-administration may be due to the direct ROS—scavenging effect of water melon juice or an increase in GSH synthesis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the decrease in the reduced glutathione level in the ethanol group is connected with ethanol induced oxidative stress and direct conjugation of GSH with acetaldehyde and other reactive intermediates of alcohol oxidation. The result of the present study agrees with the finding of Pinto et al [41] who reported that acute ethanol treatment caused reduction in the glutathione levels in different tissues. The significant increase ( P < 0.1) in the glutathione levels in the liver and brain of water melon juice treated rats prior to ethanol-administration may be due to the direct ROS—scavenging effect of water melon juice or an increase in GSH synthesis.…”
Section: Discussionsupporting
confidence: 94%
“…Acute and chronic alcohol exposures are well documented to increase the generation of reactive oxygen species (ROS). Many investigations have revealed a decreased level of antioxidants and increased production of free radicals in animals and humans following excessive ethanol exposure [41] , [42] . The protective effect of antioxidants against alcohol-induced liver injury in many studies further supports the involvement of oxidative stress [43] , [44] .…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the administration of a hop extract significantly increased the enzymatic activity of NQO1 and GST in the liver [14]. In rats, after an acute ethanol administration, XH pretreatment protected various tissues against ethanol-induced oxidative stress in a dose-dependent manner via an increase in the activity of detoxification enzymes, including GST, reduced glutathione levels, and a reduction in reactive oxygen species levels [47]. In this study, all four of the tested prenylflavonoids significantly inhibited the SULT activity in differentiated CaCo-2 cells, while 6-PN and 8-PN caused a marked increase in the SULT activity in proliferating cells.…”
Section: Discussionmentioning
confidence: 98%
“…26 Indeed, XN possesses the capacity of both inhibiting the production of free radicals in vivo and suppressing peroxidation in vitro. 12,27 Moreover, XN assuaged carbon tetrachlorideinduced acute liver damage in rats and reduced liver injury, modulated oxidative reaction in hepatitis C virus-infected Tupaia belangeri. 9,13 Hence, these results afforded interesting reference for the hepatoprotection effect of XN against INHinduced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…11 XN possesses capable of both inhibiting the production of excess ROS in vivo and suppressing peroxidation in vitro. 12 Moreover, XN also assuaged liver damage and modulated oxidative reaction in the hepatitis C virusinfected Tupaia belangeri. 13 Based on these researches, it would be of great interest to investigate whether XN possesses potential hepatoprotective effects on anti-TB druginduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 98%